Jobs, Poverty, and Working Conditions in South Asia. - World Bank Staff (Washington :: World Bank Publications, 1995)
Annotation World Development Report 1995: Workers in an Integrating World addresses labor and employment--issues that are important for South Asia. Expanding employment and increasing the remuneration of workers are essential to poverty alleviation, which is the primary objective of all countries in the region. This regional perspective examines ways in which workers in South Asia can benefit from greater integration of the global economy through improving their skills or cushioning their transition to new jobs. The paper emphasizes that governments need to develop a framework for labor policies that defines the rights of employers, workers, and labor unions and the framework for collective bargaining and settlement of disputes. Liberalization will lead to market-based development, which is the best way to raise workers' living standards--it encourages firms and workers to invest in physical capital, new technologies, and skills.
Annotation "World Development Report 1995: Workers in an Integrating World" addresses labor and employment--issues that are important for South Asia. Expanding employment and increasing the remuneration of workers are essential to poverty alleviation, which is the primary objective of all countries in the region. This regional perspective examines ways in which workers in South Asia can benefit from greater integration of the global economy through improving their skills or cushioning their transition to new jobs. The paper emphasizes that governments need to develop a framework for labor policies that defines the rights of employers, workers, and labor unions and the framework for collective bargaining and settlement of disputes. Liberalization will lead to market-based development, which is the best way to raise workers' living standards--it encourages firms and workers to invest in physical capital, new technologies, and skills.
Scholarly & Professional World Bank Publications.
Keywords: Labor and Laboring Classes -- -- Asia; Labor and Laboring Classes -- -- Developing Countries